2021
DOI: 10.14808/sci.plena.2021.054201
|View full text |Cite
|
Sign up to set email alerts
|

Peach palm and cassava wastes as biosorbents of tartrazine yellow dye and their application in industrial effluent

Abstract: In this study, the wastes from cassava (CAW) and peach palm (PPW) agro-industries were investigated as potential low-cost biosorbents for removing the tartrazine yellow dye (TAR). The by-products were prepared by washing and drying steps and characterized into physicochemical parameters and microstructure. The effects of contact time, pH, dosage and dye concentration were analyzed for the biosorbents in comparison to commercial activated carbon (AC). The biosorbents were applied to the treatment of an effluent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(91 reference statements)
0
1
0
1
Order By: Relevance
“…Tey discovered that the highest dye removal was 78 percent and that the adsorption capacity was 13.93 mg/g at an optimal concentration of 100 mg per 100 mL of dye solution. Dos Santos et al [62] studied the efect of the adsorbent dosage on removal of tartrazine yellow dye from the experimental solution by means of cassava waste biosorbents and by altering the dosage of adsorbents from 2.4 g/L to 12.4 g/L. Tey concluded that greater biosorbent concentrations encourage greater adsorption efectiveness.…”
Section: Efect Of the Adsorbent Dosagementioning
confidence: 99%
“…Tey discovered that the highest dye removal was 78 percent and that the adsorption capacity was 13.93 mg/g at an optimal concentration of 100 mg per 100 mL of dye solution. Dos Santos et al [62] studied the efect of the adsorbent dosage on removal of tartrazine yellow dye from the experimental solution by means of cassava waste biosorbents and by altering the dosage of adsorbents from 2.4 g/L to 12.4 g/L. Tey concluded that greater biosorbent concentrations encourage greater adsorption efectiveness.…”
Section: Efect Of the Adsorbent Dosagementioning
confidence: 99%
“…Uma possível aplicação de resíduos lignocelulósicos é para a produção de biossorventes (SANTOS et al, 2021;PONCE et al, 2021). Estes materiais são obtidos a partir de fontes vegetais para a adsorção de poluentes tais como corantes, metais pesados, fármacos, hormônios, etc.…”
Section: Introductionunclassified